The Cardioprotective Actions of Hydrogen Sulfide in Acute Myocardial Infarction and Heart Failure - David J. Polhemus; John W. Calvert; Javed Butler; David J. Lefer (Scientifica)
It has now become universally accepted that hydrogen sulfide (H2S), previously considered only as a lethal toxin, has robust cytoprotective actions in multiple organ systems. The diverse signaling profile of H2S impacts multiple pathways to exert cytoprotective actions in a number of pathological states. This paper will review the recently described cardioprotective actions of hydrogen sulfide in both myocardial ischemia/reperfusion injury and congestive heart failure.